OBSERVATIONAL TRAILS IN LIPIDOLOGY - S. A. Shalnova (Столичная издательская компания, 2016)
Approaches to the evaluation of drug efficacy and safety are discussed. The specifics of clinical and observational trails are presented. The trail data on statins efficacy and safety are held up as a model.